Predictors of Jaundice Resolution and Survival After Endoscopic Treatment of Primary Sclerosing Cholangitis. Issue 4 (1st September 2021) - Eaton, John E.; Haseeb, Abdul; Rupp, Christian; Eusebi, Leonardo H.; van Munster, Kim; Voitl, Robert; Thorburn, Douglas; Ponsioen, Cyriel Y.; Enders, Felicity T.; Petersen, Bret T.; Abu Dayyeh, Barham K.; Baron, Todd H.; et al.
Abstract : The benefit of endoscopic retrograde cholangiopancreatography (ERCP) for the treatment of primary sclerosing cholangitis (PSC) remains controversial. To identify predictors of jaundice resolution after ERCP and whether resolution is associated with improved patient outcomes, we conducted a retrospective cohort study of 124 patients with jaundice and PSC. These patients underwent endoscopic biliary balloon dilation and/or stent placement at an American tertiary center, with validation in a separate cohort of 102 patients from European centers. Jaundice resolved after ERCP in 52% of patients. Median follow‐up was 4.8 years. Independent predictors of jaundice resolution included older age ( P  = 0.048; odds ratio [OR], 1.03 for every 1‐year increase), shorter duration of jaundice ( P  = 0.059; OR, 0.59 for every 1‐year increase), lower Mayo Risk Score (MRS) ( P  = 0.025; OR, 0.58 for every 1‐point increase), and extrahepatic location of the most advanced biliary stricture ( P  = 0.011; OR, 3.13). A logistic regression model predicted jaundice resolution with area under the receiver operator characteristic curve of 0.67 (95% confidence interval, 0.5‐0.79) in the validation set. Independent predictors of death or transplant during follow‐up included higher MRS at the time of ERCP ( P  < 0.0001; hazard ratio [HR], 2.33 for every 1‐point increase), lower total serum bilirubin before ERCP ( P  = 0.031; HR, 0.91 for every 1 mg/dL increase), and persistence of jaundice after endoscopic therapy ( P  = 0.003; HR, 2.30). Conclusion: Resolution of jaundice after endoscopic treatment of biliary strictures is associated with longer transplant‐free survival of patients with PSC. The likelihood of resolution is affected by demographic, hepatic, and biliary variables and can be predicted using noninvasive data. These findings may refine the use of ERCP in patients with jaundice with PSC. Abstract : The benefit of endoscopic retrograde cholangiopancreatography (ERCP) for the treatment of primary sclerosing cholangitis (PSC) remains controversial. We conducted a retrospective cohort study of 124 jaundiced PSC patients who underwent endoscopic biliary balloon dilation and/or stent placement at an American tertiary center, with validation in a separate cohort of 102 patients from European centers. We found that resolution of jaundice after endoscopic therapy was associated with longer transplant‐free survival of PSC patients, and identified demographic, hepatic and biliary factors associated with successful endoscopic treatment.image